Novel Biocontrol Methods for Listeria monocytogenes Biofilms in Food Production Facilities - Gray, Jessica A.; Chandry, P. Scott; Kaur, Mandeep; Kocharunchitt, Chawalit; Bowman, John P.; Fox, Edward M. (Frontiers in Microbiology, 2018)
High mortality and hospitalisation rates have seen Listeria monocytogenes as a foodborne pathogen of public health importance for many years and of particular concern for high risk population groups. Food manufactures face an ongoing challenge in preventing the entry of L. monocytogenes into food production environments (FPEs) due to its ubiquitous nature. In addition to this, the capacity of L. monocytogenes strains to colonise FPEs can lead to repeated identification of L. monocytogenes in FPE surveillance. The contamination of food products requiring product recall presents large economic burden to industry and is further exacerbated by damage to the brand. Poor equipment design, facility layout and worn or damaged equipment can result in Listeria hotspots and biofilms where traditional cleaning and disinfecting procedures may be inadequate. Novel biocontrol methods may offer FPEs effective means to help improve control of L. monocytogenes and decrease cross contamination of food. Bacteriophages have been used as a medical treatment for many years for their ability to infect and lyse specific bacteria. Endolysins, the hydrolytic enzymes of bacteriophages responsible for breaking the cell wall of Gram-positive bacteria, are being explored as a biocontrol method for food preservation in nanotechnology and medical applications. Antibacterial proteins known as bacteriocins have been used as alternatives to antibiotics for biopreservation and food product shelf life extension. Essential oils are natural antimicrobials formed by plants and have been used as food additives and preservatives for many years and more recently as a method to prevent food spoilage by microorganisms. Competitive exclusion occurs naturally among bacteria in the environment. However, intentionally selecting and applying bacteria to effect competitive exclusion of food borne pathogens has potential as a biocontrol application. This review discusses these novel biocontrol methods, their use in food safety and prevention of spoilage, and examines their potential to control L. monocytogenes within biofilms in food production facilities.